Phosphodiesterase Type 5 Inhibitors, Sport and Doping. Issue 6 (November 2017) - Di Luigi, Luigi; Sansone, Massimiliano; Sansone, Andrea; Ceci, Roberta; Duranti, Guglielmo; Borrione, Paolo; Crescioli, Clara; Sgrò, Paolo; Sabatini, Stefania
Abstract : Phosphodiesterase type 5 inhibitors (PDE5i) ( e.g., sildenafil, tadalafil, vardenafil, and avanafil) are drugs commonly used to treat erectile dysfunction, pulmonary arterial hypertension, and benign prostatic hyperplasia. PDE5i are not prohibited by the World Anti-Doping Agency (WADA) but are alleged to be frequently misused by healthy athletes to improve sporting performance. In vitro and in vivo studies have reported various effects of PDE5i on cardiovascular, muscular, metabolic, and neuroendocrine systems and the potential, therefore, to enhance performance of healthy athletes during training and competition. This suggests well-controlled research studies to examine the ergogenic effects of PDE5i on performance during activities that simulate real sporting situations are warranted to determine if PDE5i should be included on the prohibited WADA list. In the meantime, there is concern that some otherwise healthy athletes will continue to misuse PDE5i to gain an unfair competitive advantage over their competitors.